Proceedings of the 5th SEA-DR (South East Asia Development Research) International Conference 2017 (SEADRIC 2017) 2017
DOI: 10.2991/seadric-17.2017.62
|View full text |Cite
|
Sign up to set email alerts
|

Potential Wetland Screening in Barito Kuala and Banjarmasin as Source of Science Learning

Abstract: Abstract-Learning science utilizes potential diversity of wetlands in South Kalimantan as students learning source.It will be an intermediary for students to learn about themselves and the contextual nature or closely related to everyday life. Decentralization of education brought the Indonesian education toward the development according to the potential of each area, so it needs an effort of educators to explore the diversity of wetlands to be integrated in the process of learning science as a learning source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Based on the researched development, a product was produced, namely a science module that integrates local wisdom with biotechnology which is the main discussion in class IX semester two junior high school. It makes it easier for students to complete the realm of skills and become more literate about science because learning involves local wisdom (Sya'ban et al, 2017), often found in everyday life.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the researched development, a product was produced, namely a science module that integrates local wisdom with biotechnology which is the main discussion in class IX semester two junior high school. It makes it easier for students to complete the realm of skills and become more literate about science because learning involves local wisdom (Sya'ban et al, 2017), often found in everyday life.…”
Section: Resultsmentioning
confidence: 99%
“…Secara geografis daerah ini memiliki wilayah dataran rendah yang luas yang tergolong dalam lahan basah yang meliputi lingkungan sungai, lingkungan rawa, lingkungan air tawar, lingkungan air payau dan sebagainya yang selalu tergenang air sepanjang tahun atau lingkungan air asin termasuk wilayah laut dalam di mana pada saat air pasang tidak melebihi enam meter. Lingkungan lahan basah ini juga berkaitan dengan apa saja yang ada di lingkungan tersebut baik tumbuhan dan hewan yang hidup di lingkungan tersebut, serta aktivitas manusia yang terjadi di dalamnya (Sya'ban et al, 2017).…”
Section: Pendahuluanunclassified
“…Physics material related to the Floating Market was fluid, both static fluid and dynamic fluid (Misbah, et al, 2018;Hartini, et al, 2019). The biological material related to the Floating Market as ecotourism is the environment (Normaleni, 2016;Sya'ban, et al, 2017;Stronza, et al, 2019;Wulandari, et al, 2019;Abbas, et al, 2021).…”
Section: Biophy Magazine Based On Local Wisdommentioning
confidence: 99%